2008
DOI: 10.1007/s11094-008-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxic activity of 3-triarylmethylindoles. III. 3-[Diphenyl(pyridyl)methyl]indoles

Abstract: A series of isomeric heterosubstituted 3-triarylmethylindoles were synthesized and their properties were evaluated. The activity of the synthesized compounds was found to depend on the mass of the side-chain substituent and on the position of the nitrogen atom in the heteroaromatic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…The benzylation of arenes is a classical and industrially useful Friedel–Crafts reaction for the synthesis of di‐ and triarylalkanes. An ever‐increasing number of catalytic direct activations of benzyl alcohols and benzyl acetates are nowadays being recorded 132…”
Section: Reaction With C(sp3)‐based Alkylating Agentsmentioning
confidence: 99%
“…The benzylation of arenes is a classical and industrially useful Friedel–Crafts reaction for the synthesis of di‐ and triarylalkanes. An ever‐increasing number of catalytic direct activations of benzyl alcohols and benzyl acetates are nowadays being recorded 132…”
Section: Reaction With C(sp3)‐based Alkylating Agentsmentioning
confidence: 99%
“…Die Benzylierung von Arenen ist eine klassische und industriell wichtige Friedel‐Crafts‐Reaktion zur Synthese von Di‐ und Triarylalkanen. Selbst heute noch befindet sich die Zahl neuer katalytischer direkter Aktivierungen von Benzylalkoholen und Benzylacetaten im Steigen 132…”
Section: Reaktionen Mit C(sp3)‐alkylierungsreagentienunclassified
“…Despite these developments, there have been very few studies reported in the literature pertaining to the reaction of electron-rich arenes as nucleophiles with η 3 -benzyl palladium intermediates [32,33]. In this study, it was envisioned that indole could be used as an effective nucleophile to attack benzylic systems and afford the corresponding triarylmethane compounds bearing an indole fragment, which could have numerous potential applications in organic synthesis [34][35][36][37][38][39][40]. It is noteworthy, however, that the use of indole in this way could also result in nucleophilic attack at the ortho-or para-position of the naphthyl ring, which would result in the formation of the corresponding dearomatized product through a catalytic dearomatization process [41][42][43][44].…”
mentioning
confidence: 99%